Experiences and opinions of youth towards alcohol abuse in and out of school in Oshikango, Ohangwena Region, Namibia - Chilwalo, B.N.; Makhubele, J.C.; Ananias, J.A.; Mafa, P.; Matlakala, F.K.; Hasheela, M.W.; Svinurai, A.; Freeman, R.J.; Rapholo, S.F.; Tiberia, N.H. (Technium Social Sciences Journal, 2021)
Alcohol abuse has become a global concern as heavy episodes of drinking among most youth in African countries have become prevalent. The aim of the study was to explore experiences and opinions of youth towards alcohol abuse in and out of school in Oshikango, Ohangwena Region, Namibia. This study adopted qualitative research approach and exploratory research design. Data was collected using semi structured interviews from five focused groups of in and out of school youth. For this, purposive sampling was used to sample the participants. The data was manually transcribed and thematically analysed into key subthemes. The study showed that the youth engage in alcohol related activities due to factors such as peer pressure, socioeconomic status, environmental as well as political which makes them vulnerable at the expense of their health, development and wellbeing. Their involvement in alcohol abuse is largely influenced by social modelling, perceived norms, and self-efficacy as well as outcome expectancies. The findings indicated that the environmental dynamics play a major role in the young people’s health, development and wellbeing and alcohol becomes a powerful risk factor for them to abuse. The study concludes that environment plays a big role in the way the youth learn and develop alcohol related behaviours. Furthermore, recommends that recreational facilities that are non-alcoholic to be extended to that part of the country.